Circulating MicroRNAs in Serum from Cattle Challenged with Bovine Viral Diarrhea Virus‡ - Taxis, Tasia M.; Bauermann, Fernando V.; Ridpath, Julia F.; Casas, Eduardo (Frontiers in Genetics, 2017)
Bovine viral diarrhea virus (BVDV) is an RNA virus that is often associated with respiratory disease in cattle. MicroRNAs have been proposed as indicators of exposure to respiratory pathogens. The objective of this study was to identify microRNAs in cattle that had been challenged with a non-cytopathic field strain of BVDV. Five colostrum deprived neonate Holstein calves were inoculated with BVDV (challenged) and 4 were mock challenged (control). Serum from all calves was collected at 4 different times: prior to challenge (day 0) and at 4, 9, and 16 days post challenge. RNA was extracted from sera, and expression, via read counts, of small non-coding RNAs were obtained using next-generation sequencing. A total of 905,861 sequences identified 427 microRNAs. Sixty-two microRNAs had > 1,000 total reads across all samples. Bta-miR-339a, bta-miR-185, bta-miR-486, Bta-miR-92a, bta-miR-30e-5p, bta-let-7c, and bta-miR-2284x were significantly different (P<0.05) across time regardless of challenge status. Bta-miR-423-5p (P=0.008) and bta-miR-151-3p (P=0.005) were significantly different between challenged and control animals across time. In challenged animals, bta-miR-423-5p peaked in number of reads by day 4 and steadily declined from day 4 to 16. In control animals, bta-miR-423-5p declined from day 0 to day 9 and increased in number by day 16. By day 16, both challenged and control animals had similar levels of bta-miR-423-5p, and these levels were similar to day 0 levels. Bta-miR-151-3p peaked at day 9 in challenged animals, while control animals decreased across time. By day 16, the number of reads of bta-miR-151-3p were similar between challenged and control animals. The level in challenged animals had returned to day 0 levels by day 16, whereas the levels for control animals was significantly lower (P=0.006) than day 0. Further studies are needed to establish if bta-miR-423-5p or bta-miR-151-3p could be used as a biomarker for exposure to BVDV.